Analisis Pengaruh PDRB, Pengangguran dan Indeks Pembangunan Manusia terhadap Tingkat Kemiskinan di Provinsi Jambi - Maulidin Habibi (Science of Management and Students Research Journal (SMS), 2019)
The purpose of this study was to determine and analyze the effect of GRDP, Unemployment and the Human Development Index simultaneously and passively on the level of poverty in Jambi Province. The analytical method used in this research is the analysis of secondary data, the data used in this study is time series data covering the period 2002-2016. Data analysis techniques use multiple linear regression. Based on the simultaneous test results of F count of 16,237 while with a confidence level of 95 percent df = n-k obtained F table value of 3.49 thus the calculated F is greater than the value of F table. This means that jointly the GRDP, Unemployment and the Human Development Index affect the level of poverty. Based on the partial test T table 1.7822 while the GRDP T-count (-4.288) negative and significant influence on poverty, unemployment (969) has a positive and insignificant effect on the poverty level and the Human Development Index (-098) has a negative and insignificant effect against the level of poverty. There is an influence of GRDP, Unemployment and Human Development Index in a similitude to the level of poverty. From these results it can be suggested that the government must distribute regional income fairly and equitably so that all layers of the poor can enjoy the results of economic development for the common good.